Chronic monitoring for wrongdoing as a signal of immoral character - Dhaliwal, Nathan A.; Chen, Fan Xuan; O’Reilly, Jane; Aquino, Karl (Organizational behavior and human decision processes, 2025)
•We introduce chronic monitoring for wrongdoing as a novel factor influencing the reputation of third-party actors.•Third-party punishment is often seen as less moral when it is preceded by chronic monitoring for wrongdoing.•Chronic monitoring for wrongdoing signals competitive-leveling motives and a tendency to ascribe hostile intentions to others.•We ground our research in scholarship explaining why third-party punishment signals cooperative intent. Punishing wrongdoing can sometimes have reputational benefits. But what do people think of those who regularly monitor their environment for signs of wrongdoing? Drawing on the concept of workplace vigilantism, we posit that acts of monitoring in workplace settings serve as negative cues of one’s moral character. In particular, we propose that chronically monitoring for signs of wrongdoing signals that an individual is driven by retributive and competitive leveling motives as well as a tendency to ascribe hostile motives to others. We examine this idea across six studies (and three supplementary studies). In Study 1, we find that employees have largely negative impressions of individuals who vigilantly monitor and reprimand wrongdoings at work. In Study 2, we find that punishers are seen as less moral when their acts of punishment are preceded by chronic monitoring for wrongdoing. In Study 3, we find that punishers who engage in chronic monitoring are seen as possessing heightened retributive and competitive leveling motives. In Study 4, we find that the reputational costs of chronic monitoring persist even when the violation is addressed in a courteous manner and that chronic monitoring signals that one ascribes hostile intentions to others. In Study 5, we identify an individual difference moderator, showing that negative judgments of workplace vigilantes are attenuated when observers share similar vigilante tendencies. Finally, in Study 6, we find that the reputational costs that result from chronic monitoring are observed across an array of workplace violations, including when the violation is of considerable organizational importance. Together, our results demonstrate that the perceived moral character of a punisher can hinge on whether monitoring for wrongdoing precedes such punitive acts.